Application of the Project-based Learning Model to Increase VA Students’ Creativity in Natural Science Learning at Sdn 66/IV Jambi - Muhammad Dimas Fahriansyah; Arsil Arsil; Hendra Budiono (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Classroom Action Research on VA SDN class students in natural science learning was based on initial observations, which show the students' low creativity when the teacher was still dominant in explaining the material and many students were still sitting silently. The average student's activity level is only 50%. This shows that students' creativity is still low. Therefore, the learning model that can increase students' creativity, especially in natural science learning, is Project-based Learning (PJBL). This research is Classroom Action Research to determine the effect of the PJBL model on increasing VA elementary students’ creativity. This research was conducted at SD Negeri 66/IV Jambi in April 2023. The research data was collected by observing student creativity in the learning process, teacher interviews, and documentation. The research data were analyzed qualitatively and quantitatively. The research results indicate that using the PJBL model in the learning process can increase student creativity. This improvement can be seen in data analysis for each meeting cycle. The first meeting in cycle I was 35% and the second meeting was 65% with an increase of 30%. In cycle II, the first meeting was 85% with an increase of 20% and the second meeting was 100% with an increase of 15%.